Minority or migrant? loneliness among older immigrants in England - Renee Reichl Luthra; Claudia Brunori; Alessandro Ferrara (Journal of Ethnic and Migration Studies, 2025)
Using recently available, nationally representative data on loneliness among older individuals in England, we ask: do the foreign born and their children have higher levels of loneliness than otherwise similar individuals without a migration background, and how are differences in loneliness related to both minority and immigrant experiences? In contrast to theoretical predictions, we do not find higher loneliness among the foreign born and their descendants as compared to the white British majority. However we do find that a minoritised social position, in particular exposure to discrimination, is associated with greater loneliness among those with a migration background. Immigrants who arrived later in the life course, and originated from outside the EU, are also lonelier in older age than those born in the UK or who arrived at younger ages.
Keywords: 300; Loneliness; older immigrants; older minorities; wellbeing; England